PENDIDIKAN KARAKTER PADA PONDOK PASANTREN MODERN ISLAM ASSALAAM SURAKARTA - Alfauzan Amin; Hairun Nisa (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This research aims to determine the need for sustainability in order to awaken and strengthen the awareness and also the belief of the Indonesian people that a better future must be pursued by building and strengthening the character of the Indonesian people. This study also discusses the existence of the Assalaam Islamic Modern Islamic Boarding School in forming an education program that has character and has important spiritual aspects such as memorizing the letters in the Qur'an and also the nature of Amanah which is applied with habit while at the boarding school and that is one of the character education processes that is reflected in the rules of modern Islamic boarding schools Assalaam. The research method used in this study is the Library Research method, which is a series of activities related to the method of gathering library information, reading and writing and processing research material. The data analysis technique that the authors use in this study is content analysis or what is often called content analysis. This content analysis is used to compare one research with other research in accordance with this article. It is a research that uses bibliographical sources from articles and journals to obtain research information.